The use of conductive wires for smart and protective textiles - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2016)
The aim of this study was to develop and evaluate conductive core wires reinforced cotton yarns for smart and protective textile applications. Different sensors will be attached to the developed textile structures and will employed in rehabilitation to give the patient an online feedback. The stainless steel (SS), copper (Cu) and silver treated copper (Cu/Ag) conductive wires at different diameters (40, 50 and 60 micron) were employed as the core of the Ne20 cotton yarns. A number of different yarns were produced with and without core wires. A conventional ring spinning system with an attachment was used to produce core yarns. The interaction between the yarn quality and the core wires were tested and analyzed. 20 copses of yarns were produced by using different yarn process combinations. The yarn properties were tested in terms of yarn count, yarn twist, yarn hairiness, breaking strength and elongation. As a result, the properties of cotton yarns were affected by the wire reinforcement. The tested parameters have changed in varied extents. The types of the conductive wires also had different effect on the core yarn properties. © 2015 IEEE.
Keywords: Conductive Textiles; Core Yarns; Protective Textiles; Ring Spinning